Seroprevalence of HIV, HBV, HCV and syphilis in obstetrics and gynaecology patients in West Java, Indonesia - Sari, Sri Yusnita Irda; Rachmawati, Anita; Alisjahbana, Bachti; Susanto, Herman (International Journal of Infection Control, 2015)
High prevalence rates of human immunodeficiency virus (HIV), viral hepatitis and syphilis have been reported among most-at-risks group in Indonesia, but relatively little is known about transmission of these infections to general population. The study’s objective was to determine the prevalence rate of HIV, Hepatitis B virus (HBV), Hepatitis C virus (HCV) and Syphilis infection to give indication the burden of these diseases in normal risk group which was the proxy of general population. Cross-sectional, confidential-linked anonymous serosurvey with informed consent for syphilis routine test was conducted during the period of July-September 2009 in Obstetrics and Gynaecology department of Hasan Sadikin teaching hospital in West-Java, Indonesia. Whole blood test with serum antibody was performed using rapid test for HIV, ELISA for HBV and HCV and VDRL (RPR) confirmed with TPHA test for syphilis. Descriptive data and prevalence rate of infections were calculated. Overall 797 pregnant women and gynecologist patients were participated, prevalence of HIV was 0.5% (CI 0.01-0.9), HBsAg seropositive was 2.76% (CI 1.6-3.9) while prevalence of HBeAg among HBsAg positive was 13.6% (CI 10.7-15.3). Prevalence of anti HBc was 18.4% (CI 15.3-20.6) and increased significantly with age. The prevalence rate of HCV was 1% (CI 0.3-1.7) and Syphilis was 0.25% (CI 0.09-0.5). Low prevalence of HIV infection point out that the epidemic is still concentrated in most-at-risks group while HBV and syphilis infections tend to be lower than the prevalence rate from previous study.